Realized (co)variances of eurozone sovereign yields during the crisis: The impact of news and the Securities Markets Programme. (July 2017) - Beetsma, Roel; de Jong, Frank; Giuliodori, Massimo; Widijanto, Daniel
Highlights: More news raises the volatility of yields of distressed countries. More news lowers co-variances of yields of distressed countries and Germany. There are weak news effects on yield co-variances of distressed countries. The SMP mitigates negative crisis spill-overs between distressed countries. The SMP reduces flight-to-quality from distressed countries to Germany. Abstract: We use realized variances and covariances based on intraday data to measure the dependence structure of eurozone sovereign yields. Our analysis focuses on the impact of news, obtained from the Eurointelligence newsflash, on the dependence structure. More news tends to raise the volatility of yields of financially-distressed countries and to decrease the covariance of distressed countries' yields with German bond yields, suggesting a potential flight-to-quality effect. Common news about the euro crisis and news about specific countries tend to raise the covariance of yields between distressed countries, indicating potential crisis spill-over effects. However, we do not detect spillover effects from news about third countries to the covariance between other country pairs. Bond purchases by the ECB under its Securities Markets Programme (SMP) mitigate the negative crisis spillovers among the distressed countries and reduce the potential flight-to-quality from the distressed countries to Germany.